Réponses

2014-10-30T11:29:26+01:00
Bonjour.

a/ f(5) = 5³ - 8 * 5² + 17 * 5 - 10 = 125 - 200 + 85 - 10 = 0.

b/ On factorise par x - 5.

c/ x³ - 8x² + 17x - 10 = (x - 5)(ax² + bx + c)
(x - 5)(ax² + bx +c) = ax³ + bx² + cx - 5ax² - 5bx - 5c
                            = ax³ + x²(b - 5a) + x(c - 5b) - 5c
On a alors :
ax³ = x³ ⇒ a = 1
x²(b - 5a) = -8x² ⇒ b - 5a = -8
x(c - 5b) = 17x ⇒ c - 5b = 17
-5c = -10 ⇒ c = 2
D ou le systeme :
a = 1            (1)
b - 5a = -8     (2)
c - 5b = 17    (3)
c = 2            (4)
(2) b - 5a = -8 ⇔ b - 5 = -8 ⇔ b = 5 - 8 ⇔ b = -3.
On obtient donc :
a = 1
b = -3
c = 2,
x³ - 8x² + 17x - 10 = (x - 5)(x² - 3x + 2).

d/ f(x) = 0 ⇔ (x - 5)(x² - 3x + 2) = 0
On pose :
x - 5 = 0 ⇒ x = 5
x² - 3x + 2 = 0
Δ = (-3)² - 4 * 2 = 9 - 8 = 1.
Δ > 0 ⇒ 2 solutions :
x₁ = (3 - 1) / 2 = 1
x₂ = (3 + 1) / 2 = 2
D ou S = {1 ; 2 ; 5}.

e/ f(x) > 0 ⇔ (x - 5)(x - 1)(x - 2) > 0
(suite en piece jointe).

Bon apres-midi !